2019
DOI: 10.1002/jppr.1561
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological management of common lactation problems

Abstract: The importance of breastfeeding is well recognised with benefits for both the mother and infant. Despite these benefits, women often cease breastfeeding prematurely after experiencing common problems such as breast and nipple pain or low breast milk supply in the early weeks of breastfeeding. Some mothers stop breastfeeding while taking medications to treat these conditions because of unfounded concern or inappropriate advice from healthcare providers. Most of these conditions can be managed without the need t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…A recent meta-analysis involving 390 patients ranging from infants to adults also suggested domperidone does not result in QT prolongation 44 . A previous study identified that the risks associated with domperidone among lactating women with no history of cardiac arrhythmia were less 45 . However, a recent systematic review concluded that oral domperidone usage was associated with a significantly increased risk of cardiac arrhythmia and sudden cardiac death, while most of the participants in the meta-analysis were male and elderly 46 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis involving 390 patients ranging from infants to adults also suggested domperidone does not result in QT prolongation 44 . A previous study identified that the risks associated with domperidone among lactating women with no history of cardiac arrhythmia were less 45 . However, a recent systematic review concluded that oral domperidone usage was associated with a significantly increased risk of cardiac arrhythmia and sudden cardiac death, while most of the participants in the meta-analysis were male and elderly 46 .…”
Section: Discussionmentioning
confidence: 99%